2012
DOI: 10.1371/journal.pone.0035038
|View full text |Cite
|
Sign up to set email alerts
|

Waterfowl: Potential Environmental Reservoirs of the Chytrid Fungus Batrachochytrium dendrobatidis

Abstract: Infections with Batrachochytrium dendrobatidis ( B. dendrobatidis ), the causal agent of chytridiomycosis, have been shown to play an important role in the decline of amphibians worldwide. Spread of the fungus is poorly understood. Bird movement might possibly contribute to the spread of B. dendrobatidis in the environment. Therefore, 397 wild geese in Belgium were screened for presence of B. dendrobatidis on their toes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 17 publications
0
76
0
4
Order By: Relevance
“…The effects of rates of physical contact between frogs on rates of transmission of B. dendrobatidis are not known, but frogs can also become infected by contact with water or substrates, both of which can harbour infectious B. dendrobatidis zoospores [48,49]. In addition, zoospores can be carried and released into the environment by non-amphibian hosts, including nematodes and crayfish [50,51], and non-amphibian reservoirs, including reptiles and waterfowl [52,53]. Increased calling effort could also attract predators [54], which would be detrimental for pathogen transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of rates of physical contact between frogs on rates of transmission of B. dendrobatidis are not known, but frogs can also become infected by contact with water or substrates, both of which can harbour infectious B. dendrobatidis zoospores [48,49]. In addition, zoospores can be carried and released into the environment by non-amphibian hosts, including nematodes and crayfish [50,51], and non-amphibian reservoirs, including reptiles and waterfowl [52,53]. Increased calling effort could also attract predators [54], which would be detrimental for pathogen transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of the chytrid isolate in TGhL agar and broth was examined using inverted, phase contrast, and scanning (22) and transmission electron microscopy (23). Zoospores were collected from growth on TGhL agar plates and fixed for transmission electron microscopy with s-collidine buffer followed by osmium tetroxide (23).…”
Section: B Salamandrivorans Molecular Characterization and Diagnostimentioning
confidence: 99%
“…However, this idea appeared to be temporarily abandoned after Rowley et al (17) retracted their initial report of the detection of B. dendrobatidis on nonamphibian hosts (18). Recently, it was reported that B. dendrobatidis can be carried on algae (12), terrestrial reptiles (19), waterfowl (20), and nematodes (21), but there is currently no evidence that these carriers actually supported pathogen growth or transmission, which would be necessary to explain the long-term persistence of B. dendrobatidis in the absence of amphibians. Other studies have grown B. dendrobatidis on boiled snake skin (11,22), sterilized bird feathers (23), and toe scales from waterfowl (20), but none of these studies demonstrated B. dendrobatidis growth on live hosts with functioning immune systems.…”
mentioning
confidence: 99%
“…Recently, it was reported that B. dendrobatidis can be carried on algae (12), terrestrial reptiles (19), waterfowl (20), and nematodes (21), but there is currently no evidence that these carriers actually supported pathogen growth or transmission, which would be necessary to explain the long-term persistence of B. dendrobatidis in the absence of amphibians. Other studies have grown B. dendrobatidis on boiled snake skin (11,22), sterilized bird feathers (23), and toe scales from waterfowl (20), but none of these studies demonstrated B. dendrobatidis growth on live hosts with functioning immune systems. Consequently, we lack studies that demonstrate B. dendrobatidis growth on living, nonamphibian hosts, transmission of B. dendrobatidis from these hosts to amphibians, and links between nonamphibian hosts and B. dendrobatidis prevalence in the field.…”
mentioning
confidence: 99%